Improving the Surface of Titanium Alloys with Wave Cutters; Recent Developments in the Field of Non-Destructive Testing, Safety and Materials Science; Vol. 433 : Studies in Systems, Decision and Control (SSDC) - Korovin G. I. Georgy Ivanovich; Gavrilin A. N. Aleksei Nikolaevich; Petrushin S. I. Sergey Ivanovich; Odnokopylov G. I. Georgy Ivanovich; Ermakov D. V. Dmitry Vladimirovich (2023, 2023)
Title screen